2008
DOI: 10.1186/1471-2458-8-240
|View full text |Cite
|
Sign up to set email alerts
|

Lot quality survey: an appealing method for rapid evaluation of vaccine coverage in developing countries – experience in Turkey

Abstract: Background: Vaccine-preventable diseases cause significant morbidity and mortality worldwide and in developing countries in particular. Information on coverage and reasons for non-vaccination is vital to enhance overall vaccination activities. Of the several survey techniques available for investigating vaccination coverage in a given setting, the Lot Quality Technique (LQT) remains appealing and could be used in developing countries by local health personnel of district or rural health authorities to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 4 publications
(4 reference statements)
0
32
0
Order By: Relevance
“…The findings in our study were similar to the study done by Cakir et al, in which timely age-appropriately vaccination for BCG, DPT-3, OPV-3 and Measles were 87.2%, 67%, 63.9% and 77.9% respectively. 17 Shrivastwa et al found in their study that timely administration of BCG, DPT-3 and Measles vaccines among children were present in 31%, 19% and 34% respectively. 18 It has been seen through various studies that if vaccines are given at right time and in correct doses through correct technique, effectiveness of vaccine antigens substantially increase in inducing adequate immune response in the body of children.…”
Section: Discussionmentioning
confidence: 99%
“…The findings in our study were similar to the study done by Cakir et al, in which timely age-appropriately vaccination for BCG, DPT-3, OPV-3 and Measles were 87.2%, 67%, 63.9% and 77.9% respectively. 17 Shrivastwa et al found in their study that timely administration of BCG, DPT-3 and Measles vaccines among children were present in 31%, 19% and 34% respectively. 18 It has been seen through various studies that if vaccines are given at right time and in correct doses through correct technique, effectiveness of vaccine antigens substantially increase in inducing adequate immune response in the body of children.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage was 82% in Cakir's survey which was conducted three years ago. 11 While interpreting these results it should not be underestimated that these "access times" were the declarations of the participants.…”
Section: Discussionmentioning
confidence: 92%
“…11,[13][14][15][16][17][18][19] The main reasons for common use of LQT in vaccine-related research is its ease in application, no need for a sampling frame record and/or large population size; ability to determine performance of individual sub-units in the population to identify those with "unacceptably low" coverage rates; and the possibility of chosing a range of different confidence intervals, and accuracy levels. LQAS may require a larger initial investment than administrative or cluster survey methods owing to larger sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations